Comparison of Echocardiographic and Cardiac Magnetic Resonance Imaging Measurements of Functional Single Ventricular Volumes, Mass, and Ejection Fraction (from the Pediatric Heart Network Fontan Cross-Sectional Study) - Margossian, Renee, MD; Schwartz, Marcy L., MD; Prakash, Ashwin, MD; Wruck, Lisa, PhD; Colan, Steven D., MD; Atz, Andrew M., MD; Bradley, Timothy J., MBChB; Fogel, Mark A., MD; Hurwitz, Lynne M., MD; Marcus, Edward, MSc; Powell, Andrew J., MD; Printz, Beth F., MD; et al. (The American journal of cardiology, 2009)
Assessment of the size and function of a functional single ventricle (FSV) is a key element in the management of patients after the Fontan procedure. Measurement variability of ventricular mass, volume, and ejection fraction (EF) among observers by echocardiography and cardiac magnetic resonance imaging (CMR) and their reproducibility among readers in these patients have not been described. From the 546 patients enrolled in the Pediatric Heart Network Fontan Cross-Sectional Study (mean age 11.9 ± 3.4 years), 100 echocardiograms and 50 CMR studies were assessed for measurement reproducibility; 124 subjects with paired studies were selected for comparison between modalities. Interobserver agreement for qualitative grading of ventricular function by echocardiography was modest for left ventricular (LV) morphology (κ = 0.42) and weak for right ventricular (RV) morphology (κ = 0.12). For quantitative assessment, high intraclass correlation coefficients were found for echocardiographic interobserver agreement (LV 0.87 to 0.92, RV 0.82 to 0.85) of systolic and diastolic volumes, respectively. In contrast, intraclass correlation coefficients for LV and RV mass were moderate (LV 0.78, RV 0.72). The corresponding intraclass correlation coefficients by CMR were high (LV 0.96, RV 0.85). Volumes by echocardiography averaged 70% of CMR values. Interobserver reproducibility for the EF was similar for the 2 modalities. Although the absolute mean difference between modalities for the EF was small (<2%), 95% limits of agreement were wide. In conclusion, agreement between observers of qualitative FSV function by echocardiography is modest. Measurements of FSV volume by 2-dimensional echocardiography underestimate CMR measurements, but their reproducibility is high. Echocardiographic and CMR measurements of FSV EF demonstrate similar interobserver reproducibility, whereas measurements of FSV mass and LV diastolic volume are more reproducible by CMR.